Comparison of combination of probiotic and standard therapy compared to standard therapy on eradication of Helicobacter pylori infection in children - Fransisca Theresia Aryani; Agus Firmansyah; Abdul Latief (Paediatrica Indonesiana, 2010)
Background Helicobacter pylori (H. pylori) infection is thought to be the etiology of chronic gastritis, peptic ulcer, and risk factor for gastric cancer. Management of H. pylori infection in children is associated with several problems such as compliance to therapy, untolerated side effects, and antibiotic resistance. Probiotic is reported to give beneficial effect in the management of H. pylori infection and there is no study yet on the effect of probiotic in eradication of H. pylori infection in Indonesian children.Objectives To study the effect of additional probiotic in the standard therapy on the rate of H. pylori infection eradication in children and its side effect.Methods This was a double blind randomized controlled trial performed in 23 children with H. pylori infection at Kampung Melayu and Rawa Bunga District. The diagnosis was determined based on Helicobacter pylori stool antigen test (HpSA). Subjects were randomly assigned to either receive receive amoxiycilin, clarithromycin, omeprazole, and probiotic (2 x 109 cfu of Lactobacillus acidophilus La5 and Bifidobacterium lactis Bb12) or amoxicillin, clarithromycin, omeprazole dan placebo (maltodextrin). HpSA examination was evaluated again after 2 weeks of therapy.Results Two of 13 subjects in the treatment group and 6 of 10 subjects in the control group experienced side effects. Eradication rate in the treatment group is higher than the control group (13/13 vs 7/10) but the correlation between additional probiotic with the eradication rate of H. pylori is not statistically significant.Conclusions Probiotic can reduce the incidence of side effects due to antibiotic used in H. pylori eradication (2/13 vs 6/10, p < 0.012). [Paediatr Indones. 2010;50:38-41].